2021
DOI: 10.1038/s41598-021-92889-3
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradation of Indanthrene Blue RS dye in immobilized continuous upflow packed bed bioreactor using corncob biochar

Abstract: The current study describes the aerobic biodegradation of Indanthrene Blue RS dye by a microbial consortium immobilized on corn-cob biochar in a continuous up-flow packed bed bioreactor. The adsorption experiments were performed without microbes to monitor the adsorption effects on initial dye decolorization efficiency. The batch experiments were carried out to estimate the process parameters, and the optimal values of pH, temperature, and inoculum volume were identified as 10.0, 30 °C, and 3.0 × 106 CFU mL−1,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(7 citation statements)
references
References 59 publications
0
7
0
Order By: Relevance
“…Mohanty et al. [ 72 ] also found that a bacterial consortium-BP of Bacillus fexus TS8 (BF), Proteus mirabilis PMS (PM), and Pseudomonas aeruginosa NCH (PA) was able to decolourise an anthraquinone dye Indanthrene Blue RS with a decolourisation efficiency of 100% within 9 h compared to the pure cultures of the bacterial strains which completely degraded the dyes within an average of 19 h. The researchers attributed the fast degradation of the dye by the bacteria in the consortium to the combined effect of the oxidoreductive enzymes in the reaction medium.…”
Section: Bacterial Strains Used In Degradation and Decolourisation Of...mentioning
confidence: 99%
“…Mohanty et al. [ 72 ] also found that a bacterial consortium-BP of Bacillus fexus TS8 (BF), Proteus mirabilis PMS (PM), and Pseudomonas aeruginosa NCH (PA) was able to decolourise an anthraquinone dye Indanthrene Blue RS with a decolourisation efficiency of 100% within 9 h compared to the pure cultures of the bacterial strains which completely degraded the dyes within an average of 19 h. The researchers attributed the fast degradation of the dye by the bacteria in the consortium to the combined effect of the oxidoreductive enzymes in the reaction medium.…”
Section: Bacterial Strains Used In Degradation and Decolourisation Of...mentioning
confidence: 99%
“…In recent years, research on the use of immobilized biomass materials as a filler in fixed-bed reactors to treat organic wastewater has gradually emerged, and its contribution to environmental sustainability has been significant. Mohanty et al [ 145 ] utilized corn cob BC to immobilize microbial consortia from textile wastewater and used it as a filler in a continuous up-flow fixed-bed reactor for the removal of indanthrene blue RS. The results showed that the maximum adsorption capacity of RS was 4.55 mg/g under optimal conditions (pH of 10.0, temperature of 30 ℃, and an inoculum amount of 3.0 × 10 6 CFU/mL).…”
Section: Applications Of Immobilized Biomass Materials In Bioreactormentioning
confidence: 99%
“…[9] Similarly, the decolorization rate of Anthraquinone Blue RS reached up to 90% in a continuous up-flow packed bed reactor, where Bacillus flexus TS8, Proteus mirabilis PMS, and Pseudomonas aeruginosa NCH isolated from textile wastewater, were used as the inoculum, and corn cob biochar as carrier material. [10] Research has shown that the carrier acts as a medium for biofilm proliferation, and its surface and material characteristics significantly influence biofilm properties, potentially affecting the diversity of the biofilm community. [11] Krsmanovic et al [12] emphasized the significant impact of the polymer type used in the biofilm carrier on reactor performance.…”
Section: Introductionmentioning
confidence: 99%